ABOUT THE THEORETICAL ASSESSMENT OF EFFICIENCY OF DUST COLLECTORS WITH THE COUNTER TWIRLED FLOWS IN SYSTEMS OF CLEANING OF EMISSIONS ON URBAN AIR ENVIRONMENT - Natalia Mihailovna Sergina; Elena Anatolievna Semenova; Mohammed Saif Abduljalil; Majd Ostaali (Современная наука и инновации, 2022)
At the Volgograd state architectural and construction university (ВолгГАСУ) for many years works on development and research of technical solutions of vortex inertial devices with the counter twirled flows (CTF), and also the researches directed to forecasting as the general, and fractional efficiency of these dust collectors used for decrease in level of dust pollution of urban air environment are carried out.